Novel anatomical-based surgical technique for positioning of the patellar component in total knee arthroplasty - Assi, Chahine (2017)
The patella remains one of the main sources of post-operative complication following total knee arthroplasty surgery. Optimal positioning of the patellar component is still a controversy with no clear-cut guidelines. Instead of choosing an empirical position, we described a novel surgical technique to better locate the patellar button based on the individual patellar anatomy of each patient.